Implementation of an automated robotic syringe-filling device in a hospital-based sterile products cleanroom - Trevor Rice; Alexsandra Nilges; Lindsey Amerine; Angela Yaniv (American Journal of Health-System Pharmacy, 2026)
Abstract Purpose To describe the implementation of an automated robotic syringe-filling device within a hospital-based sterile products cleanroom. Summary Automated intravenous (IV) compounding can reduce compounded product variability, decrease human error, and improve patient and staff safety outcomes. An automated robotic syringe-filling device was implemented to automate sterile syringe preparation. Staff training, workflow redesign, and batching optimization were required for effective implementation. Syringe preparation volume increased from 5,290 syringes in the first month to an average of 22,640 syringes per month by the end of the first year following implementation. Staffing needs decreased from approximately 2.5 full-time equivalents (FTEs) dedicated to manual syringe and automated bagged preparation compounding to 1.7 FTEs for combined staffing of both robots. This labor shift enabled reallocation of technician time to other high-priority tasks. Continuous process improvements increased syringe production efficiency while maintaining similar labor demands. Conclusion Robotic syringe filling significantly improved operational efficiency and capacity while reducing staff dedicated to syringe compounding. Successful implementation required thorough planning, education, and continuous improvement. As system optimization progressed, throughput gains and labor savings were realized, demonstrating the value of automation in a high-volume sterile compounding environment.